Kecerdasan Buatan dalam Pengelolaan Perpustakaan - Syaira Aulia Adhana; Anwar, Rully Khairul; Amar, Siti Chaerani Djen; Rukmana, Evi Nursanti (Universitas Islam Negeri Salatiga, 2025)
Libraries are information centers that must always keep up with the times. With the presence of increasingly sophisticated information technology, libraries can also perform cataloging and management automatically. This research aims to provide a deeper understanding of the utilization of artificial intelligence in assisting library management, knowing the positive and negative impacts of its use, as well as data security when using artificial intelligence systems. The research method used is a narrative literature review by analyzing several related journals. The results show that artificial intelligence has many benefits in improving library services, such as catalog automation, circulation, and reference services. However, there are also some risks that must be considered, such as the security of catalog data storage, the need for adequate electrical resources, and the possibility of disruptions to library services if there are problems with the system. This research concludes that the utilization of artificial intelligence in library management needs to be supported by thorough preparation, starting from technological infrastructure, the availability of skilled human resources, to data security policies. Librarians must also continue to develop their competencies in order to optimize the use of technology and provide better service to library users. Thus, libraries can continue to innovate and respond to challenges in the current era of information technology. Therefore, libraries must prepare a mature strategy in implementing artificial intelligence in order to minimize the risks that may occur.